Novel chemoselective 18F-radiolabeling of thiol-containing biomolecules under mild aqueous conditions. Issue 36 (4th April 2016) - Chiotellis, Aristeidis; Sladojevich, Filippo; Mu, Linjing; Müller Herde, Adrienne; Valverde, Ibai E.; Tolmachev, Vladimir; Schibli, Roger; Ametamey, Simon M.; Mindt, Thomas L.
Abstract : [ 18 F]FPOS: a novel prosthetic group for the chemoselective 18 F-radiolabeling of thiol-containing biomolecules under mild aqueous conditions. Abstract : We report a novel prosthetic group based on a heterocyclic methylsulfone derivative for the rapid, stable, and chemoselective 18 F-labeling of thiol-containing (bio)molecules under mild aqueous reaction conditions. Compared to established maleimide approaches, the new methodology displays some clear advantages for imaging probe development.